Congenital Anomalies Presenting as Head-Neck Swellings: A Study of 50 Cases (Bangladesh Journal of Otorhinolaryngology, 2020)
Purpose: To analyse the prevalence, distribution and presentation of different congenital head-neck lesions with their age, sex, site and side predilection.Methods: 50 patients of head-neck congenital swelling was selected from january/2013 upto december/2013 in the OPD of otorhino-laryngology, head and neck deptt. of Dhaka medical college hospital under a specific prospective study protocol.Results: The most frequent swelling was thyroglossal cyst(42%), followed by branchial arch anomalies (18%),dermoid cyst(14%),pre-auricular sinus(14%),lymphangioma(8%) and haemangioma(4%).Amongst the cervical swellings the sequential preponderence was thyroglossal cyst(52%),branchial arch anomalies(23%),dermoid cyst(13%), lymphangioma(10%) and haemangioma (2%).The majority of branchial arch anomalies(100%) were of second arch. The majority of patients were of first(52%) and second(30%) decade and the male to female ratio for thyroglossal cysts was 1:1.1.The majority of lesions were painless swelling and all were surgically excised.Conclusion: The overall frequency and age-sex distribution of congenital head-neck swellings as well as site, nature and type specific predominance of some of them in OPD of Dhaka medical college hospital are almost similar to international findings.Bangladesh J Otorhinolaryngol; October 2017; 23(2): 171-179